2016
DOI: 10.1080/10618600.2015.1062015
|View full text |Cite
|
Sign up to set email alerts
|

Parallel Resampling in the Particle Filter

Abstract: Modern parallel computing devices, such as the graphics processing unit (GPU), have gained significant traction in scientific and statistical computing. They are particularly well-suited to dataparallel algorithms such as the particle filter, or more generally Sequential Monte Carlo (SMC), which are increasingly used in statistical inference. SMC methods carry a set of weighted particles through repeated propagation, weighting and resampling steps. The propagation and weighting steps are straightforward to par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
102
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(102 citation statements)
references
References 42 publications
(45 reference statements)
0
102
0
Order By: Relevance
“…There are various existing works on parallel implementations of SMC. Amongst several others Brun et al (2002) considered particle filters in a distributed computing setting, Bolić et al (2005) devised algorithms in which interaction occurs occasionally between blocks of particles, Hendeby et al (2007) considered a GPU implementation, Vergé et al (2013) have suggested algorithms with resampling on two hierarchical levels, and Murray et al (2014) outlines some different approaches to parallel implementation of various existing resampling techniques and compares their efficiencies. Paige et al (2014) propose an algorithm substantially different form of SMC method and, which involves a branching rather than resampling mechanism, so to deal with issues of synchronicity issues.…”
Section: Resampling In Smcmentioning
confidence: 99%
“…There are various existing works on parallel implementations of SMC. Amongst several others Brun et al (2002) considered particle filters in a distributed computing setting, Bolić et al (2005) devised algorithms in which interaction occurs occasionally between blocks of particles, Hendeby et al (2007) considered a GPU implementation, Vergé et al (2013) have suggested algorithms with resampling on two hierarchical levels, and Murray et al (2014) outlines some different approaches to parallel implementation of various existing resampling techniques and compares their efficiencies. Paige et al (2014) propose an algorithm substantially different form of SMC method and, which involves a branching rather than resampling mechanism, so to deal with issues of synchronicity issues.…”
Section: Resampling In Smcmentioning
confidence: 99%
“…In our implementation, we use systematic resampling algorithm [25,26] in which the random number generation is required in resampling process. There is a study [27] to accelerate resampling in GPU-based PF. In our study, for reducing the additional overhead running random number calculation during the resampling process, we utilized thread-based running method, which is provided by host CPU, in the process of copying data to the GPU.…”
Section: Target Tracking Using Multiple State-space Modelsmentioning
confidence: 99%
“…One strategy for parallel implementation (discussed in [44] and explored in more detail elsewhere [32]) is to deliberately choose an alternative resampling algorithm such that the alternative algorithm is more amenable to parallel implementation. This paper focuses on systematic resampling specifically.…”
Section: Related Workmentioning
confidence: 99%